Relation Between vt1 vt2 and vo2max with the Special Wrestling Fitness Test in Youth Wrestlers: A Short Report - Cofre-Bolados, C; Herrera-Valenzuela, T; Sanchez-Ramirez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study investigated the relationship between peak oxygen uptake and ventilatory threshold 1 (VT1) and 2 (VT2) with the Special Wrestling Fitness Test variables. Thirteen wrestlers (male: six; female: seven) of Olympic freestyle wrestling were assessed. The Pearson’s correlation coefficient (p < 0.05) was used to establish the relationship between variables. A positive correlation was found between VT1 with throws in set B (r = 0.77; p = 0.002; 95%CI = 0.37–0.93), total throws (r = 0.73; p = 0.004; 95%CI = 0.30–0.91), heart rate recovery (r = 0.58; p = 0.036; 95%CI = 0.05–0.86), and test index (r = −0.60; p = 0.031; 95%CI = −0.86–0.07); between VT2 and throws in set B (r = 0.57; p = 0.043; 95%CI = 0.01–0.86); and between peak oxygen uptake with throws in set B (r = 0.77; p = 0.002; 95%CI = 0.39–0.93), throws in set C (r = 0.64; p = 0.02; 95%CI = 0.12–0.89), and total throws (r = 0.72; p = 0.006; 95%CI = 0.28–0.91). In conclusion, the peak oxygen uptake and ventilatory thresholds correlated with specific Special Wrestling Fitness Test variables. © 2023 by the authors.